Expressionismus : Die zweite Generation 1915-1925 - Barron, Stephanie; Gunether, Peter W.; Heckmanns, Friedrich W.; Löffler, Fritz; Roters, Eberhard; von Wiese, Stephan; Kunstmuseum Düsseldorf; Los Angeles County Museum of Art, Los Angeles; Modern Art Museum of Fort Worth, Fort Worth; Staatliche Galerie Moritzburg, Halle (München : Prestel Verlag, 1989)
Abelen, Peter ; Beckmann, Max ; Belling, Rudolf ; Berlit, Rüdiger ; Dungert, Max ; Ernst, Max ; Gotsch, Friedrich Karl ; Gramatté, Walter ; Herzog, Oswald ; Hoffmann, Eugen ; Kretzschmar, Bernhard ; Molzahn, Johannes ; Pankok, Otto ; Scharoun, Hans ; Schubert, Otto ; Wauer, William ; etc.
Expressionismus : Die zweite Generation 1915-1925, Los Angeles County Museum of Art, USA, 9. Oktober - 31. Dezember 1988 ; Modern Art Museum of Fort Worth, USA, 12. Februar - 9. April 1989 ; Kunstmuseum, Düsseldorf, BRD, 20. Mai - 9. Juli 1989 ; Staatliche Galerie Moritzburg Halle, DDr, 8. August - 30. September 1989
boek